This is tomorrow today : The Independent Group and British Pop Art - Wallis, Brian; Finkelpearl, Thomas; Alloway, Lawrence; Banham, Reyner; Barry, Judith; Frampton, Kenneth; Hamilton, Richard; Hebdige, Dick; Lawson, Thomas; Smithson, Alison & Peter; Tsai, Eugenie; Wallis, Brian; et al. (Long Island : P.S.1 The Institute for Art and Urban Resources, 1987)
Paolozzi, Eduardo ; Hamilton, Richard ; Smithson, Alison & Peter ; etc.
This is tomorrow today : The Independent Group and British Pop Art, The Clocktower, New York, October 22 - December 13, 1987
boek
Keywords: Groot-Brittannië